Dangers in Cyberspace among Children and Young People as a New Problem for Contemporary Pedagogue and Father - Anna Andrzejewska (Pedagogical Discourse, 2012)
The virtual world is attractive, far from reality, fascinating, it attracts the uniqueness of many people. Living in a virtual community allows you to overcome alienation, loneliness and isolation. Contacts on the Internet are usually less stressful and more bold than in the real world. People make online friendships and do not treat it as something fleeting. On the contrary, it happens that people who are friends through the network make up a group of people closest to us. Emotional proximity in the network in the network is reflected by the frequency with which we encounter another person, as well as by crossing roads, for example, by sharing in the same discussion groups, using similar communicators, visiting similar places. Thanks to this, closeness is experienced